Fixation Using Alternative Implants for the Treatment of Hip Fractures (FAITH-2): The Clinical Outcomes of a Multicenter 2 × 2 Factorial Randomized Controlled Pilot Trial in Young Femoral Neck Fracture Patients. Issue 10 (October 2020) - Slobogean, Gerard P.; Sprague, Sheila; Bzovsky, Sofia; Scott, Taryn; Thabane, Lehana; Heels-Ansdell, Diane; O'Toole, Robert V.; Howe, Andrea; Gaski, Greg E.; Hill, Lauren C.; Brown, Krista M.; Viskontas, Darius; et al.
Abstract : Objective: To assess whether the fixation method and vitamin D supplementation affect the risk of patient-important outcomes within 12 months of injury in nongeriatric femoral neck fracture patients. Design: A pilot factorial randomized controlled trial. Setting: Fifteen North American clinical sites. Participants: Ninety-one adults 18–60 years of age with a femoral neck fracture requiring surgical fixation. Intervention: Participants were randomized to a surgical intervention (sliding hip screw or cancellous screws) and a vitamin D intervention (vitamin D3 4000 IU daily vs. placebo for 6 months). Main Outcome Measurements: The primary clinical outcome was a composite of patient-important complications (reoperation, femoral head osteonecrosis, severe femoral neck malunion, and nonunion). Secondary outcomes included fracture-healing complications and radiographic fracture healing. Results: Eighty-six participants with a mean age of 41 years were included. We found no statistically significant difference in the risk of patient-important outcomes between the surgical treatment arms (hazard ratio 0.90, 95% confidence interval 0.40–2.02, P = 0.80) and vitamin D supplementation treatment arms (hazard ratio 0.96, 95% confidence interval 0.42–2.18, P = 0.92). Conclusions: These pilot trial results continue to describe the results of current fixation implants, inform the challenges of improving outcomes in this fracture population, and may guide future vitamin D trials to improve healing outcomes in young fracture populations. Although the pilot trial was not adequately powered to detect treatment effects, publishing these results may facilitate future meta-analyses on this topic. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.